Educate and practice - Mizusaki, Jorge Mitsuo (Scientific Journal of the Foot & Ankle, 2018)
The participation of our board review through evaluations of the articles submitted to our journal has been instrumental in the formation of the critical mass of foot and ankle surgeons centers. It becomes important in the process of academic refinement of this new generation of thinkers who should implement the technical, scientific, professional and ethical development of future surgeons in the foot and ankle area. One aspect that has stood is the need to plan the preparation of all forms of presentation of an article. Ideally, would be prospective projects with randomization, when pertinent and that would increase the position of the researcher and also our journal. It should be noted that it is available online, with easy access to all interested parties. Certainly, among our goals are the dissemination of our technical skills, our ability to create solutions, which vary point to point in our extensive territory. Efforts are made available to all medical classes. The characteristic of the foot heath care has demanded integrated multiprofessional actions, and this condition includes the treatment of diabetic feet. Nowadays, the orthopedic surgeon still acts late in these issues, however through the research and publication of papers they can act in a more close, intense and preventive way, so that the health conditions of the individuals are evaluated, protected and understood as educational actions, basic citizenship. In this way We can control, prevent deformities and catastrophic situations that affect the individual and his social environment. The actions we are developing through stimulating science is one of the pillars of Brazilian Foot and Ankle Society. We have the opportunity to provide in this fourth number of volume 12, articles that refer us to the need to integrate the multi-professional care sectors, both in public and supplementary health for people with chronic diseases such as diabetes and degenerative and rheumatic diseases. It is time to think about integrated solutions that match our professional needs; to modern and effective best practices acting as a scientific association in line with the needs of the Brazilian citizen. The wind blows favourably. Have a great reading in this period of Christmas reflections. Jorge Mitsuo Mizusaki Editor-in-chief